2017
DOI: 10.1186/s12902-017-0156-8
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol; Thyroid hormone Replacement for Untreated older adults with Subclinical hypothyroidism - a randomised placebo controlled Trial (TRUST)

Abstract: BackgroundSubclinical hypothyroidism (SCH) is a common condition in elderly people, defined as elevated serum thyroid-stimulating hormone (TSH) with normal circulating free thyroxine (fT4). Evidence is lacking about the effect of thyroid hormone treatment. We describe the protocol of a large randomised controlled trial (RCT) of Levothyroxine treatment for SCH.MethodsParticipants are community-dwelling subjects aged ≥65 years with SCH, diagnosed by elevated TSH levels (≥4.6 and ≤19.9 mU/L) on a minimum of two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 45 publications
0
58
0
1
Order By: Relevance
“…The primary and secondary outcomes at 12 months were also analyzed in prespecified subgroups according to sex and baseline thyrotropin level. 11 Analyses were repeated in the perprotocol population, which included participants who continued to take the trial regimen per the trial protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary and secondary outcomes at 12 months were also analyzed in prespecified subgroups according to sex and baseline thyrotropin level. 11 Analyses were repeated in the perprotocol population, which included participants who continued to take the trial regimen per the trial protocol.…”
Section: Resultsmentioning
confidence: 99%
“…The trial protocol, which was published previously 11 and is available with the full text of this article at NEJM.org, was approved by the relevant ethics committees and regulatory authorities in all the countries involved in the trial. Participants provided written informed consent.…”
Section: Trial Overviewmentioning
confidence: 99%
“…We believe the difference is mostly due to the significant weight of the recent study performed by Blum et al in 2018, which concluded no significant improvement of CIMT [3]. Nevertheless, the Blum study was part of the TRUST trial, which was limited to older patients (mean age was 74.4 years) [6]. In addition, in 2017, Aziz et al performed a metaanalysis that was not limited RCTs and concluded that thyroxine treatment decreased CIMT and improved lipid profile in individuals with SCH [8].…”
Section: Discussionmentioning
confidence: 97%
“…65 years and older) with SCH and concluded there was no impact on CIMT after treatment [3]. This RCT was nested within the Thyroid hormone Replacement for Untreated older adults with Subclinical hypothyroidism (TRUST) trial [6]. Despite being the largest multinational RCT examining levothyroxine treatment in the elderly population with SCH, the TRUST trial was not powered enough to detect a difference in the clinical cardiovascular outcomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Justification for these power calculations is provided in the trial protocol. 11 The methods of analysis of the continuous efficacy outcomes involving measurements at baseline and follow-up were analyzed at each time point for the comparison of the two trial groups, with adjustment for stratification variables (country, sex, and starting dose of levothyroxine) and baseline levels of the same variable with the use of multivariate linear regression (see the Supplementary Appendix). The efficacy and safety analyses were carried out in a modified intention-to-treat population, which included T h e ne w e ngl a nd jou r na l o f m e dicine participants with data on the outcome of interest.…”
Section: Resultsmentioning
confidence: 99%